Menelusuri Kearifan Pengarang Jawa melalui Kajian Relasi Tembang Macapat dengan Pesan Narasi - Luwiyanto, Luwiyanto; Nanik Herawati (PROSIDING SEMINAR NASIONAL PENDIDIKAN, BAHASA, SASTRA, SENI, DAN BUDAYA, 2023)
This research aims to describe the strategies of Javanese literary authors in the form of macapat songs through studying the relationship between macapat songs and the message or content they convey. For this purpose, the texts "Serat Seh Jangkung" by Raden Ngabehi Sumahatmaka and "Babad Pacitan" by Raden Ngabei Prawirawinata were used as data sources. The steps taken begin with reading and understanding to the two texts, then analyzed using the distributional method. The results of this study are in the form of a description of the strategy carried out by Javanese literary authors in writing literary works in the form of macapat songs. The strategy becomes a uniqueness and wisdom. This is reflected in the beautiful harmony between the message or content and the character of the song macapat as the wrapper. The macapat songs, each of which has a different character and description of events, are presented uniquely and complicatedly by the author.